Respuesta a la fertilización química del maíz hibrido `s – 3037´ sembrado en dos densidades poblacionales, en condiciones de riego - Lozano Morales, Ángel Teodoro (2011)
On the grounds of the Hacienda 'Aurora', located at Km 31, route Durán - Puerto Inca, Canton Yaguachi, Province of Guayas, a trial was testing the corn hybrid 'S - 3037', in order to assess effects of chemical fertilizer levels and population densities on the agronomic characteristics and grain yield of hybrid, identify the appropriate level of chemical fertilization and population density to maximize grain yield, and perform economic analysis of grain yield in terms the cost of treatment and undertreatment. Population densities were 71,428 and 83,333 plants per hectare, and chemical fertilizer levels were 0 - 0 - 0, 120 - 60 - 120, 150 to 70 - 150; 180 - 80 - 180, 210 - 90 - 210; and, 92 - 23 - 60 Kg / ha of nitrogen, phosphorus and potassium, respectively.